Exploring achievement-level differences in implementing self-regulated learning instruction in a classical Chinese reading intervention program - Lau, Kit Ling (Frontiers in Education, 2022)
Research on self-regulated learning (SRL) instruction typically treats students as a homogeneous group, without considering the possible effects of students’ prior level of SRL competence on the implementation and effectiveness of SRL instruction. To fill this research gap, this study explored the differences in learning outcomes among students with different achievement levels who received an SRL-based classical Chinese reading instruction program. Sixty seven ninth graders from two classes, one with high achievers and the other with moderate achievers, from one secondary school in Hong Kong participated in an intervention program designed by this study’s researchers. The study adopted qualitative methods, including classroom observations, teacher and student interviews, along with supplementary quantitative methods, including reading test and questionnaire, to explore the differences between the two achiever-groups when the intervention program was implemented. The results showed that the two classes differed on students’ SRL performance, the degree of teacher support and student autonomy, and students’ perceptions of SRL instruction. Implications of the findings for SRL research and intervention design are discussed.